The effects that influenced tours and satisfaction of unregulated ecosystem in Kampung Sungai Melayu, Johor - Muhamad Nor Firdaus Muhammad; Mohamad Afifuddin Mohd Noor; Danish Kumar Munasamy; Siti Nur Izzati Ismail (2021)
According to the Johor National Park (JNP) sources, Eco Tourism Kampung Sungai Melayu, has been proclaimed by government of Malaysia as the second national park in the peninsular Malaysia on 1993 and also the second largest of national park after Taman Negara National Park (TNNP). The objective of this research is to identify the relevance of community involvement, visitor rules and management and increasing of awareness towards tours and satisfaction of unregulated ecosystem in Kampung Sungai Melayu, Johor. The purpose of this research is to find out the best effect that influence tours and satisfaction of unregulated ecosystem in Kampung Sungai Melayu, Johor. Based on the research objectives that have been developed earlier, two research question are constructed to meet the objectives. These research question are what is the relationship between community involvement, visitor rules and management and increasing of awareness towards tours and satisfaction of unregulated ecosystem in Kampung Sungai Melayu, Johor and what is the best effect in influencing tour and satisfaction of unregulated ecosystem in Kampung Sungai Melayu, Johor. The primary research data will be collected through a structured questionnaire and SPSS software will be used for analysis process. Therefore, the research will find out the most important factor which is visitor rules and management on how to development Eco Tourism in Kampung Sungai Melayu, Johor.